Dissociation in borderline personality disorder: disturbed cognitive and emotional inhibition and its neural correlates - Winter, Dorina; Bohus, Martin; Schmahl, Christian (Psychiatry research, 2015)
Evidence is heterogeneous regarding whether patients with borderline personality disorder (BPD) display disturbed emotional inhibition in the emotional Stroop task. Previous findings suggest that state dissociation may influence cognitive inhibition of task-irrelevant material, particularly with negative content. Our aim was to examine performance in an emotional Stroop task including negative, neutral, and positive words in BPD patients and healthy controls during functional magnetic resonance imaging. In advance, half of the BPD patients underwent a dissociation induction using script-driven imagery. BPD patients without dissociation induction showed behavioural performance comparable to that of healthy controls but displayed stronger neural responses, especially to positive stimuli, in the superior temporal gyrus, dorsomedial prefrontal cortex, and anterior cingulate cortex. BPD patients with dissociation induction showed overall slower and less accurate responses as well as increased reaction times for negative versus neutral words compared with BPD patients without dissociation induction. Moreover, they showed comparatively decreased neuronal activity in the fusiform gyrus and parietal cortices independent of valence, but elevated activity in the left inferior frontal gyrus in response to negative versus neutral words. In conclusion, experimentally induced dissociation in BPD was associated with inefficient cognitive inhibition, particularly of negative stimuli, in the emotional Stroop task.
Gesehen am 09.03.2018